Pengaruh Pemberian Dosis Pupuk Cair terhadap Pertumbuhan dan Produksi Tanaman Sawi (Brassica Sinensi L.) dalam Polybag di Kelurahan Nangameting, Kecamatan Alok Timur - Mario Malado; Hendrikus Darwin Beja; Julianus Jeksen (Agriculture - Jurnal Ilmu Pertanian, 2025)
Research on the effect of liquid organic fertilizer dosage on the growth and production of mustard plants in polybags has been conducted in Nangameting Village, East Alok District, Sikika Regency. The purpose of this study was to determine the effect of liquid fertilizer dosage on the growth and production of mustard plants and to determine one of the appropriate liquid organic fertilizer dosages to increase the growth and production of mustard plants. This study used a Randomized Block Design (RAK) with five (5) treatments and (4) replications so that twenty (20) experimental units were obtained, namely: Oo (control/without fertilizer), O1 (300 ml/liquid fertilizer), O2 (600 ml/liquid fertilizer), O3 (900 ml/liquid fertilizer), O4 (1200 ml/liquid fertilizer). The results showed that the administration of liquid organic fertilizer on the height of mustard plants and the weight of fresh weight did not have a significant effect, but the placement of polybags in each group had a significant effect on the number of mustard plant leaves. The highest average base weight was found in the O3 treatment with a liquid fertilizer dose of 900 ml/polybag, namely 20.75 cm and the lowest average was in the Oo treatment without fertilizer with an average of 11.5 cm.